Toxic Relationship as Dating Violence: An Examination in the Sociology of Religion - Alda, Alda; Elsera, Marisa (BELIEF: Sociology of Religion Journal, 2024)
Individuals need other individuals to realize their potential. One of them is the need to socialize with other individuals. However, in a dating relationship, there are many conflicts including forms of dating violence such as verbal violence. Verbal violence and economic violence still happen a lot among students in Tanjungpinang. This study aims to determine how students perceive toxic relationships. To find out the social factors that cause dating violence and the social impact, this study uses a descriptive-qualitative method by examining the phenomenon of dating violence among university students by analyzing George Herbert Mead's Symbolic Interactionism theory.   Qualitative data in this study was obtained through in-depth interviews. The results showed that Toxic Relationship is internal violence. Students who are victims of dating violence do not realize they are trapped in a toxic relationship.